Теоретический анализ адресованной модификации ДНК - Перельройзен, М.П.; Вологодский, А.В. (Биополимеры и клетка, 1988)
Найдены условия, при которых может быть достигнуто максимальное соотношение между уровнями специфической и неспецифической адресной модификации ДНК. Вычислена вероятность того, что к заданному моменту времени между двумя ближайшими сайтами специфической модификации не произойдет ни одной неспецифической модификации. Знайдено умови, за яких може бути досягнуто максимальне співвідношення між рівнями специфічної і неспецифічної адресної модифікації ДНК. Обчислено ймовірність того, що до заданого моменту часу між двома найближчими сайтами специфічної модифікації не відбудеться жодної неспецифічної модифікації. Specific chemical addressed modification of DNA involves treatment of single-stranded DNA by oligonucleotides complementary to certain target sequences in this DNA and bearing groupings reactive towards the DNA bases. The binding with the partially complementary targets can cause non-specific modification. The selectivity of the addressed modification is the subject of the present investigation. Modification of a fragment is analyzed which is flanked by two target sequences complementary to a given oligonucleotide address and contains no more such exact targets over all its length. Conditions of maximum ratio between specific and non-specific modification are calculated. The probability of the process in which up to the given time both of the target termini will be specifically modified without any non-specific modification of the internal part of a fragment is determined.